Experimental and Theoretical Expansion of Access to Credit among Rural Farmers: Case Studies in Boane District, Mozambique (Global Journal of Science Frontier Research, 2020)
Abstract not found
Keywords: loans; credit; accessibility; metrics; indicators; credit terms; repayment